Chapter 12 Sámi teacher education emphasising land-based approaches for Indigenous rights - Gaup, Elisabeth Utsi; Keskitalo, Pigga; Korte, Satu-Maarit; Moore, Sylvia (Taylor & Francis, 2025)
Backed by a range of case studies and recent developments in human rights education research, Nordic Perspectives on Human Rights Education guides readers through an analysis of educational inequities and identifies how internationally agreed-upon human rights standards may inform social justice practices within schools. In an age characterised by authoritarianism and extremism, but also social and climate justice movements, this book provides a critical analysis of current practice within schools. Contributing authors also discuss how a human rights framework may improve practice, supporting intersectional thinking and more sustainable learning environments, while also empowering teachers to confidently navigate issues of gender, national identity and minority rights. Divided into three distinct sections, chapters invite readers to consider: The context behind human rights education (HRE) Rights-based approaches to teaching and education International dialogue and how we may learn from the approaches of other countries. Drawing on research from the Nordic region, and discussing its implications elsewhere, this volume is an essential resource for scholars developing theory and practice in human rights education, social studies, citizenship education and international and comparative education.